Leaf economics and plant hydraulics drive leaf : wood area ratios. Issue 4 (15th July 2019) - Mencuccini, Maurizio; Rosas, Teresa; Rowland, Lucy; Choat, Brendan; Cornelissen, Hans; Jansen, Steven; Kramer, Koen; Lapenis, Andrei; Manzoni, Stefano; Niinemets, Ülo; Reich, Peter; Schrodt, Franziska; et al.
Summary: Biomass and area ratios between leaves, stems and roots regulate many physiological and ecological processes. The Huber value H v (sapwood area/leaf area ratio) is central to plant water balance and drought responses. However, its coordination with key plant functional traits is poorly understood, and prevents developing trait‐based prediction models. Based on theoretical arguments, we hypothesise that global patterns in H v of terminal woody branches can be predicted from variables related to plant trait spectra, that is plant hydraulics and size and leaf economics. Using a global compilation of 1135 species‐averaged H v, we show that H v varies over three orders of magnitude. Higher H v are seen in short small‐leaved low‐specific leaf area (SLA) shrubs with low K s in arid relative to tall large‐leaved high‐SLA trees with high K s in moist environments. All traits depend on climate but climatic correlations are stronger for explanatory traits than H v . Negative isometry is found between H v and K s, suggesting a compensation to maintain hydraulic supply to leaves across species. This work identifies the major global drivers of branch sapwood/leaf area ratios. Our approach based on widely available traits facilitates the development of accurate models of above‐ground biomass allocation and helps predict vegetation responses to drought.